Pengaruh Manajemen Lembaga PAUD terhadap Strategi Pembelajaran Guru di Kelas - Agnesia Sitanggang; Claudia Cresensia Sembiring; Elya Siska Anggraini; Lindawati Elisabeth Nababan; Lisda Sinaga (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Early childhood education (PAUD) institution management plays a crucial role in supporting the success of classroom learning. Effective institution management can influence the learning strategies implemented by teachers in children's learning activities. This study aims to analyze the influence of PAUD institution management on teachers' classroom learning strategies through a literature review approach. The research method used was a literature review, analyzing various relevant scientific articles from the past five years. Data were obtained from indexed national journals discussing early childhood education management and teacher learning strategies. Data analysis was conducted through a process of identification, evaluation, and synthesis of relevant research findings. The study results indicate that effective PAUD institution management can support teachers in designing creative and innovative learning strategies that are aligned with the developmental characteristics of early childhood. Therefore, improving the quality of PAUD institution management is a crucial factor in enhancing the quality of classroom learning.